Education Post Covid-19 Pandemic: Teachers and Learners Construction - Agung Dwi Bahtiar El Rizaq (State Institute of Islamic Studies Imam Bonjol Padang, 2021)
The Covid-19 pandemic concequences in all of human aspect. Education is one of the main aspect that have to adapt from classical learning into virtual model. This condition that already happens at least 2 years bring various responses from both teachers and learners' perspectives. This study reveals teachers and learner's construction regarding education post Covid-19 pandemic. This reseacrh is qualitative by descriptive method. Furthermore, this study was conducted by distributing online questionnaires from 5 provinces respondents in Indonesia involving 40 teachers and 28 learners. The results of this study show that commonly, teacher get lack of technology and prefer to implement blended learning than pure vifrtual learning. From the students side, can be found that; e-learning has not fully accommodated some educational values that can transmitted through classical learning process only and blended learning is the suitable learning model for future education. Furthermore, this study recomend to identify the suitable blended learning model for sustainability of future education in every level education.